Regiocomplementary O‐Methylation of Catechols by Using Three‐Enzyme Cascades. Issue 18 (6th November 2015) - Siegrist, Jutta; Aschwanden, Simon; Mordhorst, Silja; Thöny‐Meyer, Linda; Richter, Michael; Andexer, Jennifer N.
Abstract: S ‐Adenosylmethionine (SAM)‐dependent enzymes have great potential for selective alkylation processes. In this study we investigated the regiocomplementary O‐methylation of catechols. Enzymatic methylation is often hampered by the need for a stoichiometric supply of SAM and the inhibitory effect of the SAM‐derived byproduct on most methyltransferases. To counteract these issues we set up an enzyme cascade. Firstly, SAM was generated froml ‐methionine and ATP by use of an archaeal methionine adenosyltransferase. Secondly, 4‐O‐methylation of the substrates dopamine and dihydrocaffeic acid was achieved by use of SafC from the saframycin biosynthesis pathway in 40–70 % yield and high selectivity. The regiocomplementary 3‐O‐methylation was catalysed by catechol O‐methyltransferase from rat. Thirdly, the beneficial influence of a nucleosidase on the overall conversion was demonstrated. The results of this study are important milestones on the pathway to catalytic SAM‐dependent alkylation processes. Abstract : Do you prefer meta or para ? Regioselective O‐methylation of three catechols, starting from stoichiometric amounts of ATP, methionine and catechol substrate, was achieved by use of two different catechol O‐methyltransferases. To ensure sufficient cofactor supply and to avoid product inhibition, the enzymes were used in linear cascades with a methionine adenosyltransferase and a nucleosidase.